2020
DOI: 10.21203/rs.3.rs-28822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical analysis of blood markers and imaging for diagnosis and prognosis of rheumatoid arthritis

Abstract: Background The purpose of this study is to explore the combined diagnostic value of anti-cyclic citrullinated peptide antibody (A-CCP), rheumatoid factor (RF) and imaging result in early rheumatoid arthritis, and the role of A-CCP and RF in prediction for radiological outcomes. Methods 101 patients with rheumatoid arthritis and 97 control individuals were detect their A-CCP, RF and radiological joint changes, the diagnostic efficacy of the respective indicators and the combined indicators was analyzed by logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The study concludes that the screening methods for RA includes IgM -RF and CCP assays which are superior to other RF isotypes. In another cross-sectional study done by Desheng Yang et al [2] , among 148 patients in Qingdao haici hospital, China, reported that the combined detection of ACCP and RF with imaging has a high diagnostic efficiency in the diagnosis of RA. ACCP and RF are commonly used indicators for the diagnosis, but any one test has its own limitations.…”
Section: Resultsmentioning
confidence: 99%
“…The study concludes that the screening methods for RA includes IgM -RF and CCP assays which are superior to other RF isotypes. In another cross-sectional study done by Desheng Yang et al [2] , among 148 patients in Qingdao haici hospital, China, reported that the combined detection of ACCP and RF with imaging has a high diagnostic efficiency in the diagnosis of RA. ACCP and RF are commonly used indicators for the diagnosis, but any one test has its own limitations.…”
Section: Resultsmentioning
confidence: 99%
“…However, we highlight that higher CRP values in the control group were found when compared to RA patients, which is in contrast with the RA cases from the Western population included in this study and other previously studied populations. The higher CRP levels could be an indicator of metabolic disequilibrium in any inflammatory process [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…It can be done through early and accurate diagnosis in addition to taking the appropriate doses of the improved medications for rheumatism under close observation. It infects about 25 men and 54 of women among the 100,000 population [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%